2020
DOI: 10.1186/s40792-020-00892-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid cyst within an intrapancreatic accessory spleen exhibiting abrupt changes in serum carbohydrate antigen 19-9 level: a case report

Abstract: Background: Epidermoid cyst within an intrapancreatic accessory spleen (ECIAS) is a rare disease. While the detection of solid components relevant to an accessory spleen is a key diagnostic finding, the differential diagnosis between ECIAS and malignant tumors is difficult without resection in patients with no other findings of an accessory spleen. Case presentation: A 73-year-old male was found to have an elevated carbohydrate antigen (CA) 19-9 level (95 U/mL) at an annual checkup, and a cystic lesion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, a cyst occurring in a pancreatic accessory spleen is extremely rare, with only 57 reported cases (Table 1). 8‐53 The lesion site was the pancreatic tail in all 57 cases. The primary complaints were abdominal pain and vomiting, although 33 of the 57 cases were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, a cyst occurring in a pancreatic accessory spleen is extremely rare, with only 57 reported cases (Table 1). 8‐53 The lesion site was the pancreatic tail in all 57 cases. The primary complaints were abdominal pain and vomiting, although 33 of the 57 cases were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all cases reported the dynamic changes of tumor markers. Takagi et al reported a case of epidermoid cyst within an intrapancreatic accessory spleen, which showed a sharp increase of CA19-9 before surgery and a normal serum CA19-9 level 4 weeks after surgical resection (12). Okuno et al reported an elevation of serum CEA levels in a patient with ruptured splenic epidermoid cyst, which was normalized 3 months after decapsulation (8).…”
Section: Discussionmentioning
confidence: 99%
“…Takagi et al. reported a case of epidermoid cyst within an intrapancreatic accessory spleen, which showed a sharp increase of CA19–9 before surgery and a normal serum CA19–9 level 4 weeks after surgical resection ( 12 ). Okuno et al.…”
Section: Discussionmentioning
confidence: 99%